On application of differential subordination for Carathéodory functions - Lavanya V. Agnes Sagaya Judy; Jeyaraman M. P.; Farzana H. Aaisha (Acta Universitatis Sapientiae: Mathematica, 2020)
New sufficient conditions involving the properties of analytic functions to belong to the class of Carathéodory functions are investigated. Certain univalence and starlikeness conditions are deduced as special cases of main results.